Explaining and tackling the informal economy: an evaluation of competing perspectives - Colin C. Williams (Open Economics, 2019)
This paper provides an evidence-based evaluation of the competing ways of explaining and tackling the informal economy. Conventionally, participants have been viewed as rational economic actors who engage in the informal economy when the benefits outweigh the costs, and thus participation is deterred by increasing the sanctions and/or risks of detection. Recently, however, an alternative social actor approach has emerged viewing participation to result from a lack of vertical trust (i.e., their norms, values and beliefs are not in symmetry with the laws and regulations) and horizontal trust (i.e., they believe many others are non-compliant). Reporting 2,000 face-to-face interviews conducted in Croatia in 2015, only a weak and partial association is found between participation in the informal economy and the perceived level of penalties and risks of detection, but a strong significant association with both the level of vertical and horizontal trust. Those who perceive a larger proportion of the population to be engaged in the informal economy, and those whose norms differ to the laws and regulations, display a significantly greater likelihood of participating in the informal economy. The theoretical and policy implications are then discussed.
Keywords: H26; J46; K42; O17; P37; 330; informal sector; tax morale; tax evasion; institutional theory; Croatia; South-East Europe